Sustainable business - A way to implement new jobs' - Dirk Drenk (European Regional Science Association (ERSA), 2003)
The paper gives up a summary about the possible employment effects that can arise out of sustainable business. A high employment rate in Germany has focused the view on new ways to create jobs. Parallel to this the sustainable development has become a major issue for societies all over the world. For that reason the current research standards about employment effects of sustainable business are presented. Further more a new study approach of this topic will be explained, if and to what extend sustainable business by small and medium-sized enterprises generates extra employment.
Keywords: 330